Mirabegron, a breakthrough in overactive bladder syndrome? - Almudena Maestro Nombela (Farmacia Hospitalaria, 2017)
Objective: Overactive bladder syndrome is a condition with high prevalence, which has a negative impact on patients’ quality of life. A drug with a novel mechanism of action has been recently approved: mirabegron. The objective of this study is to review the scientific evidence available on mirabegron, with the aim to analyze its efficacy, safety and cost, and thus estimate its role within current pharmacotherapy.Methods: The effectiveness and safety of mirabegron were analyzed through an evaluation of scientific evidence. The cost of different pharmacological alternatives was calculated based on their Defined Daily Dose (DDD) and their manufacturer’s sale price.Results: The use of mirabegron in the treatment of overactive bladder syndrome is supported by three randomized clinical trials, controlled with placebo, at 12 weeks. All three share the same primary efficacy variables (number of incontinence episodes per 24 hours and number of micturitions per 24 hours). Long-term efficacy data are based on a 12-month study, where efficacy outcomes were measured as secondary variables. In all studies, mirabegron showed a significant but modest effect. Some of the most frequently detected adverse effects were: hypertension, increase of glucose in blood, headache, urinary tract infections, constipation and tachycardia. Special attention must be paid to cardiovascular events. Conclusions: The clinical efficacy of mirabegron is very modest and comparable to that achieved with the other drugs approved for this indication. Moreover, it is more expensive than other therapeutic options. Cardiac risks and urinary infections only allow to consider it as an alternative option to anticholinergic drugs, when these are contraindicated, show no clinical efficacy, or cause unacceptable adverse effects.